Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.4153/cmb-2005-033-8
|View full text |Cite
|
Sign up to set email alerts
|

On Maps Preserving Products

Abstract: Abstract. Maps preserving certain algebraic properties of elements are often studied in Functional Analysis and Linear Algebra. The goal of this paper is to discuss the relationships among these problems from the ring-theoretic point of view.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…This result is connected with the well-known Hua theorem [14] and it generalizes some results of [5,10].…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…This result is connected with the well-known Hua theorem [14] and it generalizes some results of [5,10].…”
Section: Introductionsupporting
confidence: 78%
“…Now we can describe 2-local automorphisms of matrix algebras over finite-dimensional division rings using some ideas from [5,24].…”
Section: -Local Automorphisms and Derivations On Matrix Algebras Ovementioning
confidence: 99%
See 1 more Smart Citation
“…Proof Let g ∈ Lip(X). Since Φ is a 2-local isometry of Lip(X), there exists a surjective linear isometry Φˆ1 ,g of Lip(X) such that Φ(1) = Φˆ1 ,g (1) and Φ(g) = Φˆ1 ,g (g). Because the isometry group of Lip(X) is canonical, we have…”
Section: Representation Of 2-local Isometriesmentioning
confidence: 99%
“…Molnár [10] showed that every 2-local isometry of B(H) is a surjective linear isometry. Numerous papers on 2-locality have since appeared [9,11,17], and more recently [1,[5][6][7][8]18].…”
Section: Introductionmentioning
confidence: 99%